Social entrepreneurship and youth protagonism: a systematic review in the light of psychology (Research, Society and Development, 2020)
Entrepreneurship, in its social aspect, is characterized by finding creative solutions to social issues that can play a fundamental role in the development of communities. Just as the place of young people in these communities is highlighted and their possible contributions when they start to act as actors in these demands. Thus, this study aimed to carry out a systematic review of the literature, in order to understand both the phenomena "social entrepreneurship" and "youth protagonism" together, with a theoretical basis in Psychology. The methodology used was the literature review and researches were carried out on the Scielo, Pepsic, Google Scholar and Periódicos Capes databases, and academic papers that discussed both topics were analyzed. By the researches, as results there were selected 10 works that brings contributions to this objective of this article. As conclusion it is pointed to the importance of entrepreneurial education for awakening social agents to opportunities and teaching entrepreneurship techniques for the development of their businesses.